1993
DOI: 10.1258/002367793780810441
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal, segmented, filamentous bacteria in a wide range of vertebrate species

Abstract: SummarySegmented, filamentous bacteria (SFBs) form a group of bacteria with similar morphology and are identified on the basis of their morphology only. The relationships of these organisms are unclear as the application of formal taxonomic criteria is impossible currently due to the lack of an in vitro technique to culture SFBs. The intestine of laboratory animals such as mice, rats, chickens, dogs, cats and pigs is known to harbour SFBs. To see whether this extends to other animal species, intestines from 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 20 publications
0
96
0
Order By: Relevance
“…A complex microbial community was insufficient for generating a robust population of Th17 cells in the gut of SPF mice lacking SFB (9, 10) and gnotobiotic mice colonized long term with human fecal contents (42). Although SFB has been detected in multiple vertebrate species (43), there exists only sparse evidence of a related microbe colonizing humans (43)(44)(45)(46). A recent study showed that a consortium of 20 symbionts from the feces of an IBD patient could induce Th17 cells in mice but failed to identify the active microbes in healthy people (11).…”
Section: Discussionmentioning
confidence: 99%
“…A complex microbial community was insufficient for generating a robust population of Th17 cells in the gut of SPF mice lacking SFB (9, 10) and gnotobiotic mice colonized long term with human fecal contents (42). Although SFB has been detected in multiple vertebrate species (43), there exists only sparse evidence of a related microbe colonizing humans (43)(44)(45)(46). A recent study showed that a consortium of 20 symbionts from the feces of an IBD patient could induce Th17 cells in mice but failed to identify the active microbes in healthy people (11).…”
Section: Discussionmentioning
confidence: 99%
“…Specific sugar expression on the surface of the most luminal portions of mucosa throughout the rat alimentary tract in long, coccal-or rod-shaped chains between the intestinal villi of the lower part of small intestine, but never in the upper alimentary tract of rats [35]. Segmented filamentous bacteria (SFB), provisionally named Candidatus arthromitus [41], are apathogenic indigenous bacteria that colonize the lower alimentary canals, but never the upper alimentary tract of a wide range of animal species, including rats [25,27]. On the other hand, various bacterial species can bind to specific sugars on the host mucosal surface using bacterial surface lectins.…”
Section: Discussionmentioning
confidence: 99%
“…SFB have been found in about 20 vertebrate animals, including humans. and several invertebrate species (10,11). The presence of SFB with characteristic rRNA sequences in chickens, mice, and rats indicates that there has been coevolution of the SFB and their hosts, but comparisons of sequences of SFB from a greater number of animals will be required to confirm this.…”
Section: Discussionmentioning
confidence: 99%